Elderly people affected by Alzheimer´s disease: a descriptive study - Ítala Thaise Aguiar Holanda; Keila Maria de Azevedo Ponte; Mirian Calíope Dantas Pinheiro (Rev Rene)
Exploratory and descriptive study aimed at classifying the degree of dementia in elderly people affected by Alzheimer's disease using the Clinical Dementia Rating (CDR) and describing the profile of the same information provided by the family caregiver. The CDR was administered to 30 patients during home visits and their caregivers member of the Brazilian Association of Alzheimer in Fortaleza, Ceará, in 2009. The results show that patients were mostly female, married, had low education and severe dementia status. It is understood the importance of implementing multidisciplinary programs for patients and their families. As well as establishing specific actions in health education and the implementation of the CDR assessment.